Commentary: Professional Learning: A Community of Practice for Great Schools (LEARNing Landscapes, 2015)
In this interview, Linda Darling-Hammond describes the optimal way in which professional learning can be developed and implemented for teachers and school leaders. She emphasizes that teachers need to collaborate within a school and also have the opportunity to be part of a community with other schools. She explains that schools that are most successful are those where teachers, parents, and community organizations create relationships that support students inside and outside the school. As information access increases, she hopes that schools will be able to give students the skills to "learn how to learn" in order to use that information to contribute constructively to society.
Keywords: professional learning; teacher; school leader; interview; school; collaboration